Safety assessment of the process Loreco Plast Recyclage, based on the VACUNITE (EREMA basic and Polymetrix SSP V‐leaN) technology, used to recycle post‐consumer PET into food contact materials - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Andrew Chesson; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2023)
Abstract The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process Loreco Plast Recyclage (EU register number RECYC290), which uses the VACUNITE (EREMA basic and Polymetrix SSP V‐leaN) technology. The input consists of hot caustic washed and dried poly(ethylene terephthalate) (PET) flakes mainly originating from collected post‐consumer PET containers, with no more than 5% PET from non‐food consumer applications. The flakes are pre‐decontaminated in the ■■■■■ at ■■■■■ under ■■■■■ (step 2) before being extruded, pelletised and ■■■■■ (step 3). The ■■■■■ pellets are then ■■■■■ (step 4) and submitted to solid‐state polycondensation (SSP) (step 5) at ■■■■■ and under ■■■■■ and ■■■■■ in two parallel ■■■■■ lines. Having examined the challenge tests provided, the Panel concluded that step 2 as well as steps 4 and 5 are critical for determining the decontamination efficiency of the process. The operating parameters to control the performance are temperature, pressure and residence time for steps 2, 4 and 5 as well as the ■■■■■ for steps 4 and 5. It was demonstrated that this recycling process is able to ensure that the level of migration of potential unknown contaminants into food is below the conservatively modelled migration of 0.1 μg/kg food. Therefore, the Panel concluded that the recycled PET obtained from this process is not of safety concern, when used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs, including drinking water, for long‐term storage at room temperature or below, with or without hotfill. The final articles made of this recycled PET are not intended to be used in microwave and conventional ovens and such uses are not covered by this evaluation.